The Rise Of Japan’s Halal Industry And Tourism Post-Covid-19 - Januar Rizki, Mochamad; Aminah, Shobichatul (Journal Research of Social Science, Economics, and Management, 2023)
Almost this two last decades, especially in 2005, Japan has program to increase the number of visitors from overseas, including muslim visitor. This program includes Japan Halal Food Project and Muslim-Friendly Project. In addition to that, the number of tourists from overseas that came from muslim majority countries to enter Japan rose up significantly. However, COVID-19 pandemic directly affected tourism in Japan. Halal business enterprise such as restaurant, hotel, even prayer rooms and mosques had to be closed in those emergency period. Nowadays, Japan had announced opening the international borded since October 2022 thus makes Japan’s tourism slowly getting back on track especially with the presence of muslim tourists to enter Japan. This research examines the rise of halal industry and tourism in Japan Post?COVID 19 global pandemic. Using qualitative method, this research applies direct observation, interviews, and literature studis for data collection. It shows that there is an optimism from Japan’s business owners to implement the concept of halal business with the rise of muslim tourists in Japan. However, there is a rising anxiety from these owners to apply the concept due to to the dependence towards muslim tourists.